Physiological and performance responses to tournament wrestling - Kraemer, W. J.; Fry, A. C.; Rubin, M. R.; Triplett-McBride, T.; Gordon, S. E.; Perry Koziris, L.; Lynch, J. M.; Volek, J. S.; Meuffels, D. E.; Newton, R. U.; Fleck, S. J. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: The purpose of this study was to investigate the physiological and performance responses to a simulated freestyle wrestling tournament after typical weight loss techniques used by amateur wrestlers. METHODS: Twelve Division I collegiate wrestlers (mean +/- SD;19.33 +/- 1.16 yr) lost 6% of total body weight during the week before a simulated, 2-d freestyle wrestling tournament. A battery of tests was performed at baseline and before and immediately after each individual match of the tournament. The test battery included assessment for body composition, reaction/movement time, lower and upper body power and isokinetic strength, and a venous blood sample. RESULTS: Lower body power and upper body isometric strength were significantly reduced as the tournament progressed (P </= 0.05). Significant elevations in testosterone, cortisol, and lactate were observed after each match (P </= 0.05). However, there was a significant reduction (P </= 0.05) in resting testosterone values in the later matches. Norepinephrine increased significantly (P </= 0.05) after each match, whereas epinephrine increased significantly (P </= 0.05) after each match except the last match of each day. Plasma osmolality was consistently higher than normal values at all times including baseline, with significant increases observed after each match (P </= 0.05). CONCLUSIONS: Tournament wrestling augments the physiological and performance decrements of weight loss and its impact is progressive over 2 d of competition. The combined effects of these stresses may ultimately be reflected in a wrestler's ability to maintain physical performance throughout a tournament.